2024
DOI: 10.1145/3637875
|View full text |Cite
|
Sign up to set email alerts
|

The AI Ghostwriter Effect: When Users do not Perceive Ownership of AI-Generated Text but Self-Declare as Authors

Fiona Draxler,
Anna Werner,
Florian Lehmann
et al.

Abstract: Human-AI interaction in text production increases complexity in authorship. In two empirical studies (n1 = 30 & n2 = 96), we investigate authorship and ownership in human-AI collaboration for personalized language generation. We show an AI Ghostwriter Effect : Users do not consider themselves the owners and authors of AI-generated text but refrain from publicly declaring AI authorship. Personalization of AI-generated texts did not impact the AI Ghostwriter Effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 111 publications
0
5
0
Order By: Relevance
“…The AI ghostwriter effect differs from the placebo effect and the Google effect in that, at least judging from the two studies reported by Draxler et al (2024), people appear to fully be aware of generative AIs being the main driver behind the text output. In contrast to a confusion regarding the source of "googled" information (Siler et al, 2022) and unconscious effects of technology-based augmentation on the judgment of one's own abilities (Villa et al, 2023), letting an AI generate a text seems to be an intentional and conscious action that is cognitively monitored and remembered.…”
Section: Artificial Intelligence As An Unacknowledged Ghostwritermentioning
confidence: 94%
See 3 more Smart Citations
“…The AI ghostwriter effect differs from the placebo effect and the Google effect in that, at least judging from the two studies reported by Draxler et al (2024), people appear to fully be aware of generative AIs being the main driver behind the text output. In contrast to a confusion regarding the source of "googled" information (Siler et al, 2022) and unconscious effects of technology-based augmentation on the judgment of one's own abilities (Villa et al, 2023), letting an AI generate a text seems to be an intentional and conscious action that is cognitively monitored and remembered.…”
Section: Artificial Intelligence As An Unacknowledged Ghostwritermentioning
confidence: 94%
“…Another finding related to the failure to correctly attribute AI-generated work consists in the "AI ghostwriter effect" described by Draxler et al (2024). In their studies, an intricate pattern of ownership and authorship of texts emerged.…”
Section: Artificial Intelligence As An Unacknowledged Ghostwritermentioning
confidence: 99%
See 2 more Smart Citations
“…Our study is particularly informed by works that are concerned with the negative effects of language models on people's information consumption and production. In the context of co-writing with LMs, common concerns include over-reliance on AI and automationinduced complacency [45] that can lead to not only sub-optimal writing outcomes [3] but also loss of human agency and perceived ownership of the created content [11]. While over-reliance on AI's suggestions has been studied as a common issue in human-AI interaction, LMs can exert additional informational influence by exposing people to, or making it easier to express, some views more often than others.…”
Section: Human-lm Interactionmentioning
confidence: 99%